2019
DOI: 10.3390/f10020099
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy Production on Degraded Land: Landowner Perceptions in Central Kalimantan, Indonesia

Abstract: Bioenergy production from degraded land provides an opportunity to secure a new renewable energy source to meet the rapid growth of energy demand in Indonesia while turning degraded land into productive landscape. However, bioenergy production would not be feasible without landowner participation. This study investigates factors affecting landowners' preferences for bioenergy production by analyzing 150 landowners with fire experience in Buntoi village in Central Kalimantan using Firth's logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Nyamplung is already cultivated by some farmers in Wonogiri research site and shows viability for wider adoption. This is because, as our results demonstrate, there is a good financial prospect for farmers to establish nyamplung‐based cultivation systems, particularly on marginal land, helping to restore it (see also Artati et al., ).…”
Section: Resultssupporting
confidence: 52%
“…Nyamplung is already cultivated by some farmers in Wonogiri research site and shows viability for wider adoption. This is because, as our results demonstrate, there is a good financial prospect for farmers to establish nyamplung‐based cultivation systems, particularly on marginal land, helping to restore it (see also Artati et al., ).…”
Section: Resultssupporting
confidence: 52%
“…Oil palm plantations for biofuel production are exempted from ISPO certification. Indonesia has one of the most ambitious biofuel blending targets in the world, predicated on the expansion of oil palm plantations and conflicting with the National Action Plan to Reduce Greenhouse Gas Emissions (RAN-GRK) and other environmental policies (Anderson et al 2016;Artati et al 2019).…”
Section: Indonesian Sustainable Palm Oil (Ispo)mentioning
confidence: 99%
“…Marginally productive and degraded land has little value to society and provides only a fraction of the ecosystem services of natural ecosystems. FTA scientists have looked into how to transform these areas into functional landscapes with both ecological and economic value to multiple stakeholders, making the restoration of degraded lands attractive to landholders and investors alike (Baral and Lee 2016;Artati et al 2019;Duguma et al 2020).…”
Section: Managing Synergies and Trade-offs And Optimizing Landscape A...mentioning
confidence: 99%
“…Through farmer perception studies, FTA scientists identified the key conditions for farmers in degraded peatlands to integrate biomass production for bioenergy into their farming systems (Artati et al 2019). These conditions include a stable bioenergy market for landowners, use of familiar bioenergy species, and agricultural extension support for capacity building.…”
Section: Box 4 Case Study On Restoration and Bioenergy In Indonesiamentioning
confidence: 99%